Efecto del recubrimiento comestible a base de aceite esencial de residuo agroindustrial sobre las características físicas en trozos de Mangifera indica L: Effect of edible coating based on essential oil from agro-industrial residue on the physical characteristics of Mangifera indica L. pieces - Vilchez De La Cruz , Jamir Ever (2023)
Nowadays people are resuming their habit of healthy consumption, having preference to the consumption of fresh, healthy and safe products; taking with relevance the use of edible coatings; therefore, it was proposed to evaluate the effect of the edible coating based on - orange residue essential oil - (AERN) on the physical characteristics in mango pieces (Mangifera indica L), orange peels were used as raw material of the essential oil, the aromatic compound was extracted using ultrasound pretreatment. The edible coatings were formulated with orange peel essential oil and chitosan; two treatments were developed; with the variation of the percentage of essential oil (0.50 and 1.00 %) and a control sample. The mango pieces were stored refrigerated at 5°C. Physical characteristics (°Brix, pH, % titratable acidity and % weight loss) were evaluated after 8 days of storage. The results showed that the application of the edible coating helps to preserve the physical characteristics of the mango pieces. As for the control treatment (T0), 1 (T1) and 2 (T2) were obtained as final °Brix (16.7; 16.2; 16.4), final pH (3.7; 3.7; 3.7), % titratable acidity (1.8; 2.92; 2.92), % weight loss (2.03; 2.57; 1.47). Treatment 2 (composed of 1%AERN) was the most remarkable with respect to the control sample.